2014
DOI: 10.1021/jo502062z
|View full text |Cite
|
Sign up to set email alerts
|

C7-Derivatization of C3-Alkylindoles Including Tryptophans and Tryptamines

Abstract: A versatile strategy for C7-selective boronation of tryptophans, tryptamines, and 3-alkylindoles, by way of a single-pot C2/C7-diboronation–C2-protodeboronation sequence is described. The combination of a mild iridium-catalyzed C2/C7-diboronation followed by an in situ palladiumcatalyzed C2-protodeboronation allows efficient entry to valuable C7-boroindoles that enable further C7-derivatization. The versatility of the chemistry is highlighted by the gram-scale synthesis of C7-boronated N-Boc-L-tryptophan methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 207 publications
4
74
0
Order By: Relevance
“…10 Examination of conditions for the diboronation of various N-protected tryptamines demonstrated that exposure to excess pinacolborane (5 equiv), catalytic amounts of [Ir(cod)OMe] 2 , and 4,4'-di-tert-butylbipyridine in tetrahydrofuran at 60 °C, was sufficient to ensure full boronation at C2 and C7. 9 Consistent with our C2 protodeboronation hypothesis, these 2,7-diboronated indoles can be dissolved in dichloromethane followed by addition of trifluoroacetic acid to cleanly afford the desired 7-boronated indole derivatives.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…10 Examination of conditions for the diboronation of various N-protected tryptamines demonstrated that exposure to excess pinacolborane (5 equiv), catalytic amounts of [Ir(cod)OMe] 2 , and 4,4'-di-tert-butylbipyridine in tetrahydrofuran at 60 °C, was sufficient to ensure full boronation at C2 and C7. 9 Consistent with our C2 protodeboronation hypothesis, these 2,7-diboronated indoles can be dissolved in dichloromethane followed by addition of trifluoroacetic acid to cleanly afford the desired 7-boronated indole derivatives.…”
Section: Discussionsupporting
confidence: 66%
“…In all but one case (entry 1), a temperature of 60 °C and reaction time of 4-7 h was found to be ideal for the diboronation reactions (entries 2-5, Table 1). 9 These results highlighted the general compatibility of our protocol with alcohol, carbamate, ester, and sulfonamide functional groups. The excellent yield obtained for a C7-boronated tryptophan derivative (entry 4, Table 1) and its ready conversion to the corresponding 7-halo, 7-hydroxy and 7-aryl tryptophan derivatives (Scheme 1) further highlight the versatility of this chemistry.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations